Right Ventricular Function Evaluated by Tricuspid Annular Plane Systolic Excursion Predicts Cardiovascular Death in the General Population. Issue 10 (21st May 2019) - Modin, Daniel; Møgelvang, Rasmus; Andersen, Ditte Madsen; Biering‐Sørensen, Tor
Abstract : Background: Cardiovascular disease remains a leading cause of death. Right ventricular (RV) function is a strong predictor of outcome in many cardiovascular diseases, but its significance is often neglected. Little is known about the prognostic value of RV systolic function in the general population. Therefore, we aimed to determine the prognostic value of RV systolic function, evaluated by tricuspid annular plane systolic excursion (TAPSE), in predicting cardiovascular death (CVD) in the general population. Methods and Results: A total of 1039 participants from the general population without heart failure or atrial fibrillation had an echocardiogram performed and TAPSE measured. The end point was CVD. During a median follow‐up of 12.7 years (interquartile range, 12.0–12.9 years), 69 participants (6.6%) experienced CVD, whereas 162 participants (15.6%) experienced non‐CVD. Decreasing RV systolic function, assessed as TAPSE, was a univariable predictor of CVD (hazard ratio, 1.13; 95% CI, 1.07–1.20; P <0.001, per 1‐mm decrease). TAPSE remained an independent predictor of CVD after adjusting for clinical and echocardiographic parameters (hazard ratio, 1.08; 95% CI, 1.01–1.15; P =0.017, per 1‐mm decrease). Furthermore, in net reclassification analysis, decreasing RV systolic function, assessed as TAPSE, significantly improved risk classification with respect to CVD when added to established cardiovascular risk factors from the Systematic Coronary Risk Evaluation chart or a modified version of the American Heart Association/American College of Cardiology Pooled Cohort Equation. Decreasing RV systolic function, assessed as TAPSE, did not predict non‐CVD, indicating specificity for CVD. Conclusions: RV systolic function, as assessed by TAPSE, is associated with CVD in the general population. In the general population, assessment of RV systolic function may provide novel prognostic information about the risk of CVD.